Application of edge detection based on hexagonal image structure to delamination detection of carbon fiber reinforced polymer material. (1st April 2022) - Chen, YongQiang; Luo, Kai; Chen, Liang; Weng, Haobo; Liang, Wei
Abstract: Delamination is one of the most critical damage modes in carbon fiber reinforced polymer (CFRP) materials, and is invisible to the naked eye. Although delamination defect images of CFRP materials can be obtained through ultrasonic tomography, it is still difficult to accurately identify the position and contours of defect images. In this study, four different delamination defect images of CFRP composite plates were obtained through a finite element simulation and fan-beam ultrasonic tomography. A hexagon algorithm based on interpolation is proposed that transforms the reconstructed defect images from square pixels into hexagonal pixels. The interpolation algorithm is based on the overlap between the square and hexagonal pixels. As the experiment results verify, the use of the hexagonal structure-based morphological method for edge detection significantly reduces the recognition error from 7.74% to 0.148% in comparison with a traditional quadrilateral structure. The experimental results also showed that this method can effectively reduce the artifact interference and obtain complete and accurate target edge information more effectively than a square structure.